Napaka v ogledalu procesa učenja tujega jezika - Pirih Svetina, Nataša (Jezik in slovstvo, 2003)
The paper presents a method of error analysis as one of the possible approaches in analysing and interpreting the language production of learners ofa foreign language, in this case and, as illustrated by examples, Slovene. The error is defined as a failed part of language and as a form or a combination of forms produced by the learner. These forms would not have been produces by native speaker in the same context and the same sort of circumstances. Steps in error analysis are presented briefly: from data collection, error identification, error description, classification, to evaluation.
Keywords: jezkikovna didaktika; Slovene; slovenščina; slovenščina kot drugi ali tuji jezik; tuji jeziki; napake